BULLYING HANDLING STRATEGY IN REALIZING ISLAMIC SOCIALISM IN BANDAR KLIPPA VILLAGE, PERCUT SEI TUAN DISTRICT - Panjaitan, Naura Hamidah; Muniruddin (International Journal of Cultural and Social Science, 2025)
Bullying is a complex problem that significantly impacts individuals' mental, social, and spiritual development. This research aims to analyze the causative factors of bullying, its effects on victims and perpetrators, and to formulate handling strategies based on Islamic values in Percut Sei Tuan District. Using a descriptive qualitative method, data were obtained through in-depth interviews with five key informants, participatory observation, and documentation study, which were then analyzed thematically. The results show that bullying is caused by disharmonious family factors, social environmental pressure, and weak supervision from educational institutions and the community. The impacts include psychological disturbances such as trauma and anxiety, social isolation, and decreased academic performance in victims, while perpetrators develop continuous aggressive behavioral patterns. Effective handling strategies identified include character education based on Islamic values, cooperation between schools and parents, community education, and religious-based approaches through Islamic counseling. This research concludes that the integration of Islamic values such as rahmah (compassion), 'adl (justice), and ukhuwah (brotherhood) in bullying handling strategies can create a more harmonious and conducive social environment for individual development.